Effects of motivational audio on running distance and perceived effort in recreational running - Hilman Farid Mohamed Aris (Nanyang Technological University, 2021)
Music has been widely used to accompany any form of exercise, especially running. The rising popularity of podcasts has created new sources of inspirational motivational audio. Recreational runners now have the choice of listening to such audio or their own preferred music in hopes of running longer distances with lower perceived effort, which can improve their fitness and well-being. The purpose of this study was to investigate and compare the effects of using motivational audio, self-selected music and no music on running distance and perceived effort. 13 recreationally active male runners (Age: 23.77 ± 1.17 years old; Body Mass Index: 22.16 ± 1.91 kg/m2) were recruited to participate in a within-subjects randomised experimental design. Participants underwent 3 self-paced 12-minute running sessions on a 400-metre running track, each while listening to 3 different conditions (motivational audio, self-selected music and no music). Distance was measured using the Nike Run Club application and rate of perceived exertion (RPE) values were collected every 3 minutes using Borg’s (1982) CR-10 Scale. Results indicated that both motivational (p= 0.022) and self-selected music (p= 0.047) can significantly increase running distance than no music. However, no significant differences (p= 0.622) were observed between the 2 music conditions. There were also no significant differences (p= 0.747) in RPE across all 3 conditions. Conclusively, audio intervention can improve physical performance of running further with a similar amount of effort. The use of motivational audio now presents itself as a viable alternative to self-selected music in producing a more efficient run.